Growth, maturation and ripening of underutilized Carissa congesta fruit - Ding, Phebe; Mashah, Nor Cahaya (E D P Sciences, 2016)
Introduction. Carissa congesta (syn. C. carandas L.) belongs to the family Apocynaceae. It is a sprawling semi-vine shrub native to India, Nepal, Sri Lanka, Malaysia, Thailand, Myanmar and China. However, it is categorized as an underutilized tropical fruit. One of the important prerequisites for the establishment of a fruit is to understand its growth and nutritional value changes as the fruit develops. Thus, this study was undertaken to study C. congesta fruit growth patterns and its compositional changes during maturation and ripening. Materials and methods. A total of 300 flowers at the full bloom stage were tagged randomly. The longitudinal and equatorial diameters of 34 fruits were measured every two weeks using a digital calliper until fruit had ripened. Compositional changes such as peel color, firmness, soluble solid concentration, titratable acidity, pH and vitamin C content of fruit were assessed from week 8 after flower full bloom until fruit had ripened. Results and discussion. The growth of C. congesta fruit exhibited a single sigmoidal curve, as measured by longitudinal and equatorial diameters. The peel color changed from pink to light red, and finally to dark purple, corresponding with the chromaticity values. The firmness of fruit decreased, while the soluble solid concentration increased as fruit matured and ripened. The increase in pH was paralleled by a decrease in the titratable acidity and content of vitamin C. Conclusion. Maturation and ripening affected the fruit nutritional composition of C. congesta. This fruit contains high vitamin C and it is worth exploring its potential as a new fruit crop for fresh consumption and processing.